Efisiensi Ekonomi Faktor Produksi Pada Usahatani Brokoli (Brassica Oleracea Varietas Italica Plenck) - Yohanes Kosmas Fernandez (BiSTeK Pertanian, 2021)
Broccoli is One of horticultural crops that have high nutritional fiber. Broccoli (Brassica oleracea) is a vegetable plant included in the tribe or Brassicaceae family. These vegetables come in Indonesia not long ago (around 1970) and quite as food now. It was containing vitamin C and dietary fiber in large quantities, so the broccoli is important for the human body needs. The availability of the means or factors of production (input) means that productivity is not obtained by farmers will be high. Less precise application of technology resulted in low production and high cost of farming. According Zulkifly (2009) in farming, production produced will be good if the factors of production used efficiently. To get maximum benefit the farmers must use precisely the factors of production, and combines optimally and efficiently. Therefore, it is necessary to pnelitian about the economic efficiency of production factors in usatani in general, especially in the farming of broccoli.